Sustainable Development: A Policy Model of Environmental in Kampung Hijau Bandar Lampung - Junaidi, Junaidi; Muhammad Guntur Purboyo , Muhammad Guntur Purboyo; Azis Amriwan , Azis Amriwan; Usman Raidar, Usman Raidar; Yuni Ratnasari, Yuni Ratnasari; Teuku Fahmi, Teuku Fahmi (JOURNAL OF GOVERNMENT SCIENCE, 2025)
The sustainable development model can provide space for changes that can create prosperity for society. Therefore, consistency in implementing sustainable development must be supported by a more concrete policy direction at the empirical level. The aim is to be an instrument in realizing prosperity in the context of sustainable development. Therefore, the study of the Kampung Hijau sustainable development model is important. This study was conducted through a literature review supported by a qualitative approach with a case study method. Therefore, the data sources in this study are mostly secondary data. However, to observe the conditions empirically, this research is still supported by primary data obtained through interviews and observations. This study further explores how sustainable development can serve as an analytical tool in research. The results of this study indicate that, at the practical level, the Kampung Hijau development model, particularly in Teluk Betung Selatan District, provides space for community welfare. Therefore, this development model can be used as a more concrete and broader policy direction in realizing the development model in certain areas, such as slums and rural areas.